Popular and Nationality Values Oriented on Indonesian Legal Science Reform - Suhadi, Suhadi (Law Research Review Quarterly, 2016)
Popular values led by wisdom wisdom is one of the values that should be an orientation in the formation of Indonesian law. With this value, the resulting law is not only democratic but also guided by wisdom wisdom which is oriented to the benefit of the nation, not to groups, groups or individuals. Through the development of populist values-oriented legal science, legal products produced will have a responsive, even progressive, pro-life and welfare character of the Indonesian nation.